Cultural tradition and organization of Chacayán, pasqueña community - Ramírez Bautista, Bernardino (2010)
This study develops the evolution and trends of the most important aspects that define a rural current community as Chacayán; its history, resources, economy, level of development, its entail with the State, its commoners organized in neighborhoods and hamlets, as well as its cultural expressions with roots in the popular tradition.